2022
DOI: 10.3844/erjsp.2022.30.41
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Efficient Thermal Conversion Technologies and HHV from Compositional Characteristics of Cassava Peelings, Plantain Peelings and Corn Cobs

Abstract: The understanding of compositional characteristics permits to predict the efficient thermal conversion technologies and Higher Heating Value (HHV). Although HHV can be determined directly, many models have been proposed for HHV prediction. They are based on proximate, ultimate, and structural analysis and require much data collected. The present work assesses to predict efficient thermal conversion technologies and HHV of the most abundant agricultural biomass from Cameroon, namely cassava peelings, plantain p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This diminishes its usefulness as a fuel source. Consequently, high MC leads to a decrease in HHV . It was revealed that lemongrass, sawdust, and cashew leaves had the lowest MC and hence a high HHV.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This diminishes its usefulness as a fuel source. Consequently, high MC leads to a decrease in HHV . It was revealed that lemongrass, sawdust, and cashew leaves had the lowest MC and hence a high HHV.…”
Section: Resultsmentioning
confidence: 99%
“…Through thermochemical conversion technologies, the HHV and FC contents are increased by carbon content . Hydrogen content also contributes to increase the HHV value while nitrogen has the opposite effect . The oxygen content is the most vital fuel property because it gives the combustion behavior of the fuel.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations